Influence of Various Factors on Circulating 25(OH) Vitamin D Concentrations in Dogs with Cancer and Healthy Dogs. (23rd September 2017) - Weidner, N.; Woods, J.P.; Conlon, P.; Meckling, K.A.; Atkinson, J.L.; Bayle, J.; Makowski, A.J.; Horst, R.L.; Verbrugghe, A.
Abstract : Background: Low blood 25‐hydroxyvitamin D (25(OH)D) concentrations have been associated with cancer in dogs. Little research has examined what other factors may affect 25(OH)D concentrations. Objectives: (1) To determine whether the presence of cancer (lymphoma, osteosarcoma, or mast cell tumor [MCT]) in dogs is associated with plasma 25(OH)D concentrations and (2) identify other factors related to plasma 25(OH)D concentrations in dogs. Animals: Dogs newly diagnosed with osteosarcoma (n = 21), lymphoma (n = 27), and MCT (n = 21) presented to a tertiary referral oncology center, and healthy, client‐owned dogs (n = 23). Methods: An observational study design was used. Dietary vitamin D intake, sex, age, body condition score (BCS), muscle condition score (MCS), and plasma concentrations of 25(OH)D, 24, 25‐dihydroxyvitamin D (24, 25(OH)2 D) (a marker of CYP24A1 activity), as well as ionized calcium (ICa), parathyroid hormone, and parathyroid hormone‐related protein concentrations were measured. An analysis of covariance was used to model plasma 25(OH)D concentrations. Results: Cancer type ( P = 0.004), plasma 24, 25(OH)2 D concentrations ( P < 0.001), and plasma ICa concentrations ( P = 0.047) had significant effects on plasma 25(OH)D concentrations. Effects of age, sex, body weight, BCS, MCS, and plasma PTH concentrations were not identified. A significant interaction between ICa and cancer was found ( P = 0.005). Plasma 25(OH)D concentrations increased as ICa concentrations increased in dogs with cancer, whereas plasma 25(OH)D concentrations decreased as ICa concentrations increased in healthy dogs. Conclusions and Clinical Importance: Results support a relationship between cancer and altered vitamin D metabolism in dogs, mediated by plasma ICa concentrations. The CYP24A1 activity and plasma ICa should be measured in studies examining plasma 25(OH)D concentrations in dogs.